Penerapan Model Perluasan Theory of Planned Behavior untuk Menyelidiki Niat Beli Produk Makanan Organik - Chitra Annisa Ramadhaningtyas; Chairiza Azmi; Refli Renaldi; M.A Jaya Damanik (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the extended Theory of Planned Behavior (TPB) in predicting purchase intentions of organic food products. It investigates the influence of environmental awareness, environmental knowledge, attitudes toward organic food, subjective norms, and perceived behavioral control on the intention to purchase organic food among young consumers in Indonesia. Using purposive sampling, data were collected from 100 respondents through an online questionnaire and analyzed using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) approach. The results show that environmental knowledge has a positive and significant effect on attitudes toward organic food, whereas environmental awareness does not significantly influence attitudes. Furthermore, attitudes, subjective norms, and perceived behavioral control positively and significantly affect purchase intention. However, environmental awareness and environmental knowledge do not have a direct significant impact on purchase intention. These findings suggest that internal psychological factors play a more dominant role than external factors in influencing the intention to buy organic food.